En passant learning of music theory in choirs; teaching and teacher education implications for South African conductors - Michael Barrett-Berg; Caroline van Niekerk; Roy Page-Shipp (Social Sciences and Humanities Open, 2023)
Fifteen experienced South African conductors were interviewed on the importance of Music Theory for choristers, and its inculcation. All agreed on the value of some knowledge and understanding of Music Theory. They reflected particularly on its contribution to rapid learning and satisfying performance of items in their repertoire. Although not the main purpose of rehearsal, all conductors endeavour to improve this knowledge and understanding, illustrating the importance of Music Theory concepts as prompted by the needs of the music. Illustrations should be tailored to choristers’ maturity and experience, but gratifying improvements in insight and competence result in all cases.